2011
DOI: 10.1099/mic.0.051565-0
|View full text |Cite
|
Sign up to set email alerts
|

The glgB-encoded glycogen branching enzyme is essential for glycogen accumulation in Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum transiently accumulates glycogen as carbon capacitor during the early exponential growth phase in media containing carbohydrates. In some bacteria glycogen is synthesized by the consecutive action of ADP-glucose pyrophosphorylase (GlgC), glycogen synthase (GlgA) and glycogen branching enzyme (GlgB). GlgC and GlgA of C. glutamicum have been shown to be necessary for glycogen accumulation in this organism. However, although cg1381 has been annotated as the putative C. glutamicum glgB g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…(16)(17)(18)(19)(20) It has also been suggested that bacteria make distinct forms of glycogen depending on their environment. Bacteria like Enterobacteria, that live primarily in other organisms where food is relatively plentiful, tend to have glycogen made up of longer average glucan chains, while organisms that must survive for extended periods outside of a host, in relatively hostile environments, tend to produce glycogen with much shorter average glucan chains.…”
mentioning
confidence: 99%
“…(16)(17)(18)(19)(20) It has also been suggested that bacteria make distinct forms of glycogen depending on their environment. Bacteria like Enterobacteria, that live primarily in other organisms where food is relatively plentiful, tend to have glycogen made up of longer average glucan chains, while organisms that must survive for extended periods outside of a host, in relatively hostile environments, tend to produce glycogen with much shorter average glucan chains.…”
mentioning
confidence: 99%
“…In a similar manner, transcription of the genes glgC, glgA, and glgB for glycogen synthesis is induced in cultivations with glucose and repressed in cultivations with acetate (42,44). The two global regulators RamA and RamB are involved in the control of glgC and/or glgA transcription; however, the substrate-dependent transcriptional control of these two genes is brought about by an as-yet-unknown regulator (44).…”
Section: Discussionmentioning
confidence: 84%
“…For quantification of ␣-glucan degradation products, the bicinchoninic acid assay was used as described previously (42). Glucose solutions (0 to 25 M) were used for the calibration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Branching enzymes have been described in a variety of organisms, including plants [Carciofi et al, 2012;Huang et al, 2013;Kang et al, 2013;Yandeau-Nelson et al, 2011], animals [Lee et al, 2011;Ward et al, 2004;Ziemssen et al, 2000], fungi [Matsumoto et al, 1990] and bacteria [Roussel et al, 2013;Seibold et al, 2011]. However, only a few of these branching enzymes have been shown to be active at high temperatures.…”
Section: Introductionmentioning
confidence: 99%